2017
DOI: 10.1371/journal.pone.0173641
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression is positively associated with lymph node metastasis in nasopharyngeal carcinoma

Abstract: BackgroundAccumulating evidence has demonstrated that cyclooxygenase-2 (COX-2) is involved in head and neck cancers, especially in nasopharyngeal carcinoma (NPC). However, the association between COX-2 expression and lymph node metastasis in NPC remains uncertain. This systematic review and meta-analysis meta-analysis investigated the relationship between COX-2 expression and lymph node metastasis and other signs of disease progression in NPC.MethodsPreviously published studies assessing COX-2 expression and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Bin Yang et al, also discovered the same result related to COX-2 overexpression and malignant process, including metastasis [ 26 ]. A study conducted by Gui Yang et al, also found that COX-2 and advanced clinical stage of NPC are positively correlated (OR 5.39; 95% CI: 3.79-7.66) [ 27 ]. Also, One study conducted by Li et al found by using nasopharyngeal carcinoma cell lines treated with nonsteroid anti-inflammatory drugs (NSAIDs), particularly celecoxib, invasion, and migration will decrease through suppression of MMP-2 and -9 activity 28 Fendri et al, also discovered the similar result related to COX-2 overexpression that There was a significant association between COX-2 expression with lymph node involvement (N+) in NPC patients with p < 0.0001 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bin Yang et al, also discovered the same result related to COX-2 overexpression and malignant process, including metastasis [ 26 ]. A study conducted by Gui Yang et al, also found that COX-2 and advanced clinical stage of NPC are positively correlated (OR 5.39; 95% CI: 3.79-7.66) [ 27 ]. Also, One study conducted by Li et al found by using nasopharyngeal carcinoma cell lines treated with nonsteroid anti-inflammatory drugs (NSAIDs), particularly celecoxib, invasion, and migration will decrease through suppression of MMP-2 and -9 activity 28 Fendri et al, also discovered the similar result related to COX-2 overexpression that There was a significant association between COX-2 expression with lymph node involvement (N+) in NPC patients with p < 0.0001 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipases and prostaglandins are known to be intimately connected to inflammatory and degenerative processes and to increase concentrations in these situations (HUDSON et al 2016;YANG et al, 2017). In the reproductive field, the inflammatory process of the endometrium in postpartum can be exemplified: the COX-2 enzyme is responsible for mobilization of arachidonic acid for PGE production (HUDSON et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Radiotherapy and chemotherapy can alleviate disease progression in NPC patients. Nevertheless, a high proportion (70–80%) of NPC patients have lymph node and distant metastasis at presentation, which limits the efficacy of treatment . The possible reasons for poor outcome are likely to be multifactorial and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a high proportion (70-80%) of NPC patients have lymph node and distant metastasis at presentation, which limits the efficacy of treatment. 2 The possible reasons for poor outcome are likely to be multifactorial and complex. Sensitive and specific biomarkers are needed not only for the early detection of NPC, but also for obtaining more comprehensive and accurate data to improve outcome.…”
Section: Introductionmentioning
confidence: 99%